JURIDICAL REVIEW OF MORTGAGE RIGHTS GUARANTEES IN CREDIT AGREEMENTS ACCORDING TO LAW NUMBER 4 OF 1996 CONCERNING MONITORING RIGHTS: - Henry Aspan; Rahmad Mirad; Ami Natuz Zahara (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Risks that generally occur in providing credit facilities are failure or delays in repayment of credit (credit risk), risks arising from market movements (market risk), risks due to the bank being unable to fulfill its maturing obligations (liquidity risk), and risks due to there are weaknesses in the juridical aspect caused by legal demands, the absence of supporting legislation (legal risks). In Article 1 number 11 of Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking, the definition of credit is formulated "Credit is the provision of money or bills that can be equated with it based on an agreement or loan agreement between the Bank and the other party. others that require the borrower to pay off the debt after a certain period of time with interest." Law Number 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land and makes the interests of debtors and creditors receive legal protection from the government. The main objective of enacting the Mortgage Rights Law is, in particular, to provide legal protection for creditors if the debtor commits an unlawful act in the form of a default. If the debtor breaks his promise, the object of the Mortgage Rights is sold through a public auction according to the method specified in the applicable laws and regulations and the holder of the Mortgage Rights has the right to take all or part of the proceeds to pay off his receivables, with pre-emptive rights over other creditors.